Induction of functional Brm protein from Brm knockout mice - Thompson, Kenneth W. (Oncoscience, 2015)
Once the knockout of the Brm gene was found to be nontumorigenic in mice, the study of BRM's involvement in cancer seemed less important compared with that of its homolog, Brg1. This has likely contributed to the disparity that has been observed in the publication ratio between BRG1 and BRM. We show that a previously published Brm knockout mouse is an incomplete knockout whereby a truncated isoform of Brm is detected in normal tissue and in tumors. We show that this truncated Brm isoform has functionality comparable to wild type Brm. By immunohistochemistry (IHC), this truncated Brm is undetectable in normal lung tissue and is minimal to very low in Brmnull tumors. However, it is significant in a subset (~40%) of Brg1/Brm double knockout (DKO) tumors that robustly express this truncated BRM, which in part stems from an increase in Brm mRNA levels. Thus, it is likely that this mutant mouse model does not accurately reflect the role that Brm plays in cancer development. We suggest that the construction of a completely new mouse Brm knockout, where Brm is functionally absent, is needed to determine whether or not Brm is actually tumorigenic and if Brm might be a tumor suppressor.